Effect of dauricine on myocardial contraction force and coronary circulation - ZHU Jie-quan; JIA Ju-fang; YAN Hong-wen; HU Chong-jia (Acta Pharmacologica Sinica; Vol 7, No 6 (November 1986): Acta Pharmacologica Sinica, 2016)
In isolated rat hearts, dauricine (Dau) increased coronary arterial flow, inhibited myocardial contraction force and slowed heart rate in a dose-dependent manner. Effects of Dau, verapamil (Ver) and propranolol (Pro) on myocardial blood flow of mice were studied by 86RbCl-extraction method. Ip Dau 50 mg/kg, Ver 7.5 mg/kg increased the blood flow, whereas Prof 30 mg/kg decreased it. Prof counteracted the increase of myocardial blood flow by isopreterenol, while Dau did not. On the other hand, Dau and Ver markedly antagonized the increase of myocardial blood flow by CaCl2. The results indicate that the effect of Dau on myocardial blood flow differers from the beta-receptor blocking agent Pro, but similar to Ver and probably related to the antagonism to calcium.